2021
DOI: 10.1007/s00703-021-00803-3
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high speed video observations of intracloud lightning flash initiation

Abstract: This study describes results from video observations of five intracloud flashes located ≤ 20 km from the camera and recorded with 6.1 µs exposure time and 6.66 µs frame intervals. Video data are supported with electric field change (E-change) and VHF measurements, with emphasis on the flash initiating event (IE) and initial breakdown (IB) stage. In four of the five flashes, the IE is accompanied by weak luminosity, ≤ 5% above background, lasting for 300–500 µs. Two of these four IEs were positive Narrow Bipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In addition, the initial event of this flash appears at around 156.8 ms corresponding to only a subtle burst of the 337 nm radiance in Figure 2c with no distinguishable signal occurs in the 777.4 nm band, consistent with observations from the high‐speed videos that only a little or no visible luminosity coincident with the initial events (Stolzenburg et al., 2021). Here, we further suggest the weak luminosity of this initial event could be created by streamers due to the absence of 777.4 nm radiance (Soler et al., 2020).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, the initial event of this flash appears at around 156.8 ms corresponding to only a subtle burst of the 337 nm radiance in Figure 2c with no distinguishable signal occurs in the 777.4 nm band, consistent with observations from the high‐speed videos that only a little or no visible luminosity coincident with the initial events (Stolzenburg et al., 2021). Here, we further suggest the weak luminosity of this initial event could be created by streamers due to the absence of 777.4 nm radiance (Soler et al., 2020).…”
Section: Resultssupporting
confidence: 85%
“…Rare optical observations of cloud‐to‐air flashes (Edens et al., 2014; Krehbiel et al., 2008; Stolzenburg et al., 2021) have discussed the highly intermittent features, the light‐emitting patterns, and the escaping behaviors of cloud‐to‐air flashes. For IC flashes, luminosity measurements from ground‐based photometric instruments have been presented (Stolzenburg et al., 2016, 2022; Wilkes et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by groundlevel observations of Jacobson et al (2013), (table 5), who reported that out of 193 lower-level CIDs (see figure 8(a)) only 2 (1%) were accompanied by optical (350-1100 nm) signals and none out of 24 upper-level CIDs did so. More recently, Stolzenburg et al (2021), (figures 5 and 11), from ultra-high speed (6.1 μs exposure time) video observations, reported on faint luminosity enhancements in the 350-1060 nm (with peak at 670 nm) range associated with two lower-level CIDs.…”
Section: Cids and Initiation Of Full-fledged Lightning Flashesmentioning
confidence: 95%
“…Stolzenburg et al. ( 2021 ) analyzed five IC flashes and in four of them reported faint light emissions (⩽5% above background cumulative intensity) at the time of the IEs. Recently López et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the physical mechanism of fast breakdowns of the initial type NBEs (Rison et al, 2016;Wu et al, 2014) remains poorly understood. Stolzenburg et al (2021) analyzed five IC flashes and in four of them reported faint light emissions (⩽5% above background cumulative intensity) at the time of the IEs. Recently López et al (2022) investigated the initiation of four lightning flashes detected from LMA and simultaneous optical satellite observations and found that, in three of the flashes, the detection of blue emissions without any red luminosity supports the pure streamer nature of fast breakdown processes at the flash initiation.…”
mentioning
confidence: 99%